Underemployment in the early careers of college graduates following the Great Recession - Jaison R. Abel; Richard Deitz (Federal Reserve Bank of New York, 2015)
Though labor market conditions steadily improved following the Great Recession, underemployment among recent college graduates continued to climb, reaching highs not seen since the early 1990s. In this paper, we take a closer look at the jobs held by underemployed college graduates in the early stages of their careers during this period. We show that relatively few recent graduates were working in low-skilled service jobs, and that many of the underemployed worked in fairly well paid non-college jobs requiring some degree of knowledge and skill. We also find that the likelihood of being underemployed was lower for those with technically oriented and occupation-specific majors than it was for those with degrees in more general fields. Moreover, our analysis suggests that underemployment is a temporary phase for many recent college graduates as they transition to better jobs after spending some time in the labor market, particularly for those who start their careers in low-skilled service jobs.
Keywords: I23; J23; J24; J62; 330; college graduates; college major; great recession; labor market dynamics; STEM; underemployment